Enhancing Student Financial Literacy through Collaborative Value Creation in West Java - Nanda Ravenska; Sulaeman Rahman Nidar (Trescode Green Organization, 2024)
Financial literacy education is essential for students as it provides a strong foundation for managing their finances in the future. This study aims to evaluate the effectiveness of creating a value process in increasing students' financial literacy and determine what components need to be optimized in OJK of West Java Province's collaboration program and their partners based on the Collaborative Value Creation (CVC) Framework. The research method used is descriptive qualitative with data collection techniques through semi-structured interviews and documentation. The collaboration by OJK of West Java Province has been effective but can be optimized to achieve transformational collaboration, which has the most significant impact on partners and the wider community. Among the five components that need to be improved are collaborative value-creation processes and the need to measure the impact of collaborative programs or activities on participants who receive financial education.